2007
DOI: 10.1007/s00787-007-0650-z
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Depression Inventory in Estonia

Abstract: The aim of study was to estimate the score of symptoms of depression with the Children's Depression Inventory (CDI) among Estonian schoolchildren aged 7-13-year-old, according to age and gender differences, and to identify the components in factor analysis characterising self-reported childhood symptoms of depression. The applicability of the CDI in 7-year-old children was also estimated. The number of subjects in the study was 725 (342 girls and 383 boys), and the mean age was 10.2 (SD 1.7). The mean total sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In light of this finding, we focused on this period in order to detect features of depression in a sample of Italian adolescents. The CDI mean score found in our sample was comparable to the one observed in other studies using the same tool, carried out on Italian ( Poli et al, 2003 ; Pantusa et al, 2006 ), Estonian ( Samm et al, 2008 ), Hungarian ( Piko and Balázs, 2012 ) and extra-European ( Twenge and Nolen-Hoeksema, 2002 ) samples. Also the percentage of adolescents reporting a depressive level above the risk threshold was consistent with results of other studies using this same self-report questionnaire in Italy ( Frigerio et al, 2001 ; Poli et al, 2003 ) and in other countries ( Masip et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In light of this finding, we focused on this period in order to detect features of depression in a sample of Italian adolescents. The CDI mean score found in our sample was comparable to the one observed in other studies using the same tool, carried out on Italian ( Poli et al, 2003 ; Pantusa et al, 2006 ), Estonian ( Samm et al, 2008 ), Hungarian ( Piko and Balázs, 2012 ) and extra-European ( Twenge and Nolen-Hoeksema, 2002 ) samples. Also the percentage of adolescents reporting a depressive level above the risk threshold was consistent with results of other studies using this same self-report questionnaire in Italy ( Frigerio et al, 2001 ; Poli et al, 2003 ) and in other countries ( Masip et al, 2010 ).…”
Section: Discussionsupporting
confidence: 90%
“…Results of previous research focusing on gender differences in depressive symptomatology were quite inconsistent: although most studies observed a higher depressive level in females than in males ( Poli et al, 2003 ; Piko and Balázs, 2012 ), other studies did not detect gender differences ( Samm et al, 2008 ) or found males scoring higher than females ( Kovacs, 1992 ). Findings of our research revealed only a slightly higher level of depressive symptoms in girls, as compared with boys.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The scores can also be interpreted by dividing responses into five categories: negative mood, interpersonal problems, ineffectiveness, anhedonia, and negative self-esteem (25,26). Several studies carried out in North America and Europe (including Croatia) investigated the psychometric characteristics of the scale, and corroborated its reliability and validity (25,27-30). According to Croatian standardization data, the Cronbach coefficient was satisfying (α = 0.82) (29).…”
Section: Methodsmentioning
confidence: 84%